Hubungan Kepuasan Kerja Terhadap Kinerja Karyawan yang Bekerja Tidak Sesuai dengan Pendidikan di Yogyakarta - Amanda Hana Pratiwi; Annisa Warastri (EduInovasi: Journal of Basic Educational Studies, 2025)
The mismatch between education and work shows that the world of education is not yet fully able to bridge the needs of the current world of work as a whole. This research aims to determine whether or not there is a relationship between employee performance and job satisfaction for employees whose work does not match their educational background in Yogyakarta. The variables of job satisfaction and workload are measured using a scale. The subjects of this research were 100 employees whose work did not match their educational background. The data analysis test used in this research was the Product Moment method using Windows SPSS version 26. Based on the results of 100 employee participants working in Yogyakarta, the correlation between employee performance and job satisfaction showed a correlation coefficient value of 0.498 with a significance value of ρ = 0.000 (ρ < 0.05) then these results can be said to mean that there is a positive and significant relationship between employee performance and job satisfaction. The higher the performance of employees working in Yogyakarta, the higher the job satisfaction of employees working in Yogyakarta.